2019
DOI: 10.1111/mmi.14430
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro DNA phosphorothioate modification reaction

Abstract: Phosphorothioation (PT) involves the replacement of a nonbridging phosphate oxygen on the DNA backbone with sulfur. In bacteria, the procedure is both sequence‐ and stereo‐specific. We reconstituted the PT reaction using purified DndCDE from Salmonella enterica and IscS from Escherichia coli. We determined that the in vitro process of PT was oxygen sensitive. Only one strand on a double‐stranded (ds) DNA substrate was modified in the reaction. The modification was dominant between G and A in the GAAC/GTTC cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Besides the presence of PglZ, the common feature of all BREX systems is the presence of ATPase and methyl transferase. In the Type IV systems, the latter is replaced by a PAPS reductase, an enzyme that can be involved in DNA phosphorothioation [192]. The most prevalent is the Type I BREX and systems of this type have been experimentally investigated in B. subtilis, E. coli, and V. cholerae (where it has been found in the SXT conjuga tive elements) [191,193,194].…”
Section: Bacteriophage Exclusion Systems (Brex)mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the presence of PglZ, the common feature of all BREX systems is the presence of ATPase and methyl transferase. In the Type IV systems, the latter is replaced by a PAPS reductase, an enzyme that can be involved in DNA phosphorothioation [192]. The most prevalent is the Type I BREX and systems of this type have been experimentally investigated in B. subtilis, E. coli, and V. cholerae (where it has been found in the SXT conjuga tive elements) [191,193,194].…”
Section: Bacteriophage Exclusion Systems (Brex)mentioning
confidence: 99%
“…The PT modification occurs as a result of the activi ty of the system of dndABCDE genes (Dnd is a phenotype associated with DNA degradation), which encode the DndA cysteine desulfurase, the DndC PAPS reductase, the DndD ATPase/nicking endonuclease, and a small protein DndE that binds nicked DNA, while DndB regu lates transcription of the dndBCDE operon and deter mines proportion of the PT modified sites in the genome [204, 207 209]. Not all stages of the biochemical pathway involved in PT modification have been determined but it is known that cysteine serves as a donor of the sulfur atom that is transferred to DndC and next incorporated in an energy dependent manner into the DNA that was pre liminary nicked at specific sites by DndD [192,210,211]. Recently, it was shown that the dnd genes could also be BIOCHEMISTRY (Moscow) Vol.…”
Section: Bacteriophage Exclusion Systems (Brex)mentioning
confidence: 99%
“…The contradiction between the in vivo and in vitro results prompted us to construct a mutant strain, HY1, expressing the chromosomal dndBCDE operon in which a single cysteine residue (C280) was replaced with a serine residue in DndC. The single-point C280S mutation completely abolished the DNA PT modification ( 35 ), but the complete DndCDE protein complex was retained. Interestingly, despite the loss of the DNA PT modification, torC in the HY1 strain displayed the same transcription level as that in wild-type Cerro 87 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IscS (a DndA homolog), DndC, DndD, and DndE have been observed to form a complex at an approximate molecular ratio of 1:1:1:1 in vitro ( 34 ). A recent study showed that DndCDE-IscS confers the DNA PT modification in the presence of SAM, Mg 2+ , ATP, and cysteine, supporting the PT reaction through a radical SAM mechanism ( 35 ). All these observations suggest that sulfur is first transferred from cysteine to DndA and then to the cysteine residues in DndC before it is ultimately incorporated into the DNA backbone through the coordinated functions of DndD and DndE ( 36 ).…”
Section: Introductionmentioning
confidence: 95%
“…Recently, another PT-modifying gene cluster has been reported, sspA-D , which confers cells with 5′-C ps CA-3′ on the single strand [ 4 ]. The DndA protein, which can be functionally substituted by an IscS (a cysteine desulfurase located elsewhere in the genome) [ 5 , 6 ], transfers sulfur into the Fe-S cluster of DndC [ 5 , 7 ]. SspA and SspD may share the same initial sulfur mobilization pathway with DndA and DndC, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%